Matematică
loreloredana1
2

Efectuati urmatoarele calcule: a) (x-2)(x+1)+3x(x-3)-2(x²-3x-4) b)- [latex] \frac{1}{3} [/latex]x²·(-3y)²+0,5x·(-4xy²)-8[latex] x^{4} [/latex][latex] y^{6} [/latex]:(-2xy²)²+[latex] \frac{4}{15} [/latex]x²:(-[latex] \frac{2}{5} [/latex])·3y²

+0
(1) Răspunsuri
Magdalazanu

a) (x-2)(x+1)+3x(x-3)-2(x²-3x-4)= x²-x-2+3x²-9x-2x²+6x+8= 2x²-4x+6= 2(x²-2x+3)= 2(x-3)(x+1) b)-1/3x²·(-3y)²+0,5x·(-4xy²)-8x⁴y⁶:(-2xy²)²+4/15x²:(-2/5)·3y²= -1/3x²·9y²+(-2x²y²)-8x⁴y⁶:4x²y⁴+4/15x²:(-2/5)·3y²= -3x²y²-2x²y²-2x²y²-2x²y²= -9x²y²

Adaugă răspuns